Junior High School Student’s Understanding Mathematics Concepts in Solving Problems of Flat-Sided Three Dimensional - Fina Fanoni; Eny Suryowati (Journal of Education and Learning Mathematics Research (JELMaR), 2022)
Understanding the concept can be seen from the process of solving problems by paying attention to students' abilities. Conceptual understanding in this study is based on students' processes of restating and using concepts that have been learned, using relationships between concepts, and using routine procedures with operations needed to solve math problems. The purpose of this study is to describe the understanding of students' mathematical concepts in solving flat-sided three dimensional problems based on mathematical abilities. This research is a descriptive qualitative research. Collecting data in this study using test and interview methods, the instruments used test sheets and interview guidelines. The research subjects were 3 grade IX students of SMP Negeri 1 Gudo who were selected based on their mathematical ability. Subjects consist of one student who has high mathematical ability, one student who has moderate mathematical ability, and one student who has low mathematical ability. Data analysis was carried out in three stages, namely data reduction, data presentation and conclusion drawing. Based on data analysis, it was found that subjects who had high and moderate abilities restated and used the concepts they had learned, used relationships between concepts, and used routine procedures with operations needed to solve math problems. Subjects who have low mathematical ability restate and use the concepts that have been learned, cannot use the relationship between concepts and cannot solve math problems correctly.